Mechanisms of DNA repair by recombination - Haber, James (Henry Stewart Talks, 2009)
Genome instability in tumor cells, Mutations, Loss of heterozygozity, Repair of chromosome breaks, Double-strand break repair is essential for life, Replication stalling and fragile sites, Programmed DSBs, Repair of DSBs arising during DNA replication by recombination, The homologous recombination machinery, E. coli, Holliday junctions, Break-induce replication, Single strand annealing, Types of homologous recombination, Observing DNA repair in real time, Molecular studies of recombination, Nonhomologous end-joining (NHEJ) pathways, Copy number variation, Gene amplification